2021
DOI: 10.1016/j.heliyon.2021.e08118
|View full text |Cite
|
Sign up to set email alerts
|

Concept generation of cognitive enhancement: healthcare professionals' approach towards the impact and utilization of cognitive enhancers in academic context

Abstract: Cognitive enhancers (CEs) encompass a wide range of drugs, including prescription medications for attention deficit disorders and pharmacological compounds for cognitive enhancement. It is well-documented that the students are the leading cohort of CEs users. Exploring how healthcare professionals perceive the use of CEs for academic accomplishments is significant to understand their encouragement of CE use. Hence, the purpose of the current study was to look at healthcare professionals' attitudes and perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, there has been no exact data or previous studies that reported the prevalence misuse of CEs in UAE, it only indicated that 86% of male and female students in Zayed University (UAE) showed a positive attitude towards coffee consumption as a CE (Ghali et al., 2016). Several studies show a concerning increase in the use CEs among adult students in an attempt to improve academic achievement (e.g., Monnet et al., 2021; Narayanan et al., 2021; Shakeel et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there has been no exact data or previous studies that reported the prevalence misuse of CEs in UAE, it only indicated that 86% of male and female students in Zayed University (UAE) showed a positive attitude towards coffee consumption as a CE (Ghali et al., 2016). Several studies show a concerning increase in the use CEs among adult students in an attempt to improve academic achievement (e.g., Monnet et al., 2021; Narayanan et al., 2021; Shakeel et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Research reported that the spread of CE use is increasing year-on-year in the US, which is an alarming indicator for society figures that should encourage them to stand firmly against it (Greely et al, 2008;Lucke et al, 2018). Moreover, some university students believe that using CEs gives them an opportunity to increase and improve the quality of their studies and academic achievement (Ragan et al, 2013;Volkow et al, 2008) andShakeel et al (2021) also added that CEs can make the purpose of study. The current qualitative study showed that the most common prescribed drugs used among students in (Part I) was 'Adderall' and for nonprescribed drugs it was caffeine supper strength pills, which is aligned with previous studies (Sharif et al, 2022).…”
Section: Theme (3): Raising a Campaignmentioning
confidence: 99%
See 1 more Smart Citation